Proposal for a physiotherapy assessment form for the evaluation of women patients with uro-gynecological disorders: A Delphi study. - Ana González-Castro; Raquel Leirós-Rodríguez; Óscar Rodríguez-Nogueira; Mª José Álvarez-Álvarez; Arrate Pinto-Carral; Elena Andrade-Gómez (PLoS ONE)
Background The correct selection of treatment techniques and methods in physiotherapy depends directly on a well-structured anamnesis, examination and assessment. Within urogynecological and obstetric physiotherapy there is no standardized and protocolized assessment that allows to follow established steps. For all this, the main objective of this study was to identify the assessment items that should be included in the a physiotherapeutic uro-gynecological assessment. Methods Delphi study through a group of experts. Prior to this, a systematic search was carried out, accompanied by a review of grey literature, to obtain the possible items to be included in the forms. Subsequently, a Delphi study with two consecutive rounds of questionnaires was developed. A total of 6 expert physiotherapists participated in the study. Results The initial questionnaire had 97 items and after two rounds one item was eliminated to obtain a total of 96 items in the final questionnaire. Conclusions The experts agreed on most of the choices and finally obtained a standardized and protocolized assessment in uro-gynecological physiotherapy. Furthermore, this proposal should be considered by other professionals involved in the process of evaluation and treatment of pelvi-perineal alterations.